SOFT SKILLS TRAINING FOR STUDENTS BEFORE PARTICIPATING IN AN INTERNSHIP - Supriyono; Baby Poernomo; Md. Ahsan Habib (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Internships are essential for students because they provide hands-on work experience, enhance skills, and help build professional networks. This allows students to apply the theories learned in class in the real world of work, thus strengthening their understanding and increasing their readiness for future careers. Unfortunately, until now there are still many complaints from companies or agencies that accept interns. In general, companies complain about things related to soft skills. This study aims at answering the questions of This study aims to answer the question of how the soft skills competencies of students who take part in internships are and what should be done to improve the quality of students' soft skills. In this study, researchers did semi structured interviews to 10 students who had participated in internships at companies and government agencies to find out what kind of preparation was provided by the campus before they participated in the internship. Researchers also interviewed 10 Human Resources Managers at the companies to find out how the students' soft skills competencies were during the internship.  The result of this study indicates that training of soft skills is very important for universities to provide to students before they take part in internships. This is because soft skills such as communication, collaboration, leadership, and adaptability are very much needed in the world of work and can help students adapt better during internships.